1984
DOI: 10.1029/jb089ib08p06857
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of viscosity on the dynamics of replenished magma chambers

Abstract: Some aspects of the dynamical behavior of magma chambers, replenished from below with hotter but denser magma, have been modeled in a series of laboratory experiments. In previously reported work the fluids used were aqueous solutions of comparable viscosity, and thus the results should be applicable to basaltic magma chambers, in which the magmas do not vary greatly in viscosity. In that case, the lower layer cools by convective heat transfer to the fluid above, and crystallization causes the density of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 24 publications
1
36
0
2
Order By: Relevance
“…Previous work has considered magma mixing using analogical, numerical or experimental approaches [8][9][10][11][12][13][14][15][16][17][18][19][20] , which have all yielded valuable information on the fluid mechanics, leading to efficient stirring. However, the rigorous evaluation of the conditions favourable to intimate magma mixing has been hampered by the difficulty of simulating mixing at high pressure, and by the complex fluid-mechanical behaviour of magmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has considered magma mixing using analogical, numerical or experimental approaches [8][9][10][11][12][13][14][15][16][17][18][19][20] , which have all yielded valuable information on the fluid mechanics, leading to efficient stirring. However, the rigorous evaluation of the conditions favourable to intimate magma mixing has been hampered by the difficulty of simulating mixing at high pressure, and by the complex fluid-mechanical behaviour of magmas.…”
mentioning
confidence: 99%
“…The injection of denser basalt into a lighter reservoir most likely produces viscous gravity currents spreading at the floor, leading to a stratified two-layer system 15 , except when excess momentum is available, which may induce fountaining 16 . Ensuing crystallization can lead to density inversion producing either local 17,18 or wholesale 19 overturning and associated mixing/mingling, depending on viscosity contrast 20 . Observations and fluid dynamical considerations [8][9][10][11][12][13][14][15][16][17][18][19][20][21] have shown that, in calcalkaline reservoirs, mixing/mingling most likely starts either from such boundary layer instabilities 17 , with centimetre to decimetre wavelength scale 18 , or from breakup of injected magma dykes 12 .…”
mentioning
confidence: 99%
“…Assuming anhydrous conditions and temperatures of 1,140-1,115°C, and based on the model of Giordano et al (2008), the calculated viscosities of the LP and HP liquid phases range between 10 2.5 and 10 3.4 Pa s, decreasing by one order of magnitude under hydrous conditions (10 1.3 -10 2.4 for H 2 O 1-2 wt.%). The analogous and relatively low viscosities of the melts (i.e., the liquid phases) can further enhance the efficiency of magma mixing (Huppert et al 1984;Campbell and Turner 1986;Bateman 1995). Chaotic mingling of poorly viscous melts, along with chemical diffusion, can account for the chemical exchanges that produced domains of intermediate composition (Perugini et al 2003;De Campos et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…마그마 혼합의 양상은 마그마 상호간에 작용하는 여러 가지 요인들 중에서 점성 차이가 매우 중요한 역할을 한다 (Huppert et al, 1984;Campbell and Turner, 1985;Blake and Campbell, 1986). Vernon, 1984;Castro et al, 1990).…”
Section: 혼성작용의 메카니즘unclassified